Not to Instantly Increase Manuscript Quantity, but to Accelerate Breakthroughs in Psychology: The Essence of Letter to the Editor (LtE): [Bukan Untuk Meningkatkan Kuantitas Naskah Secara Instan, Melainkan Mengakselerasi Terobosan di Bidang Ilmu Psikologi: Intisari Surat Kepada Editor] - Abraham, Juneman; Siaputra, Ide Bagus (ANIMA Indonesian Psychological Journal, 2023)
In the field of psychology, we witness and experience rapid development of ideas about humans, especially in the era of the Industrial Revolution 4.0, where psychology will accept the influence of cybernetic ideas. As a researcher in psychology who is diligent in observing human behavior, repeatedly in our minds, various "hypotheses" about the dynamics of human behavior complexes emerge. Especially in Indonesia, the fertile place where the complex dynamics is wrapped in cultural diversity. It is urgent to publish these “hypothetical thoughts” - also a response to the results of peer studies - in a solid, communicative, and persuasive form; so that it can be followed up by peers with pleasure. This is one of the pathways for the development of psychological science which, honestly and regretfully, is still rare by scientific journals of psychology in Indonesia. The way we communicate psychological science, thus, is no longer "accommodated" by one or two forms of scientific publications, such as original articles or reviews (both narrative and systematic). The world of Indonesian scientific publications can learn from the world of journalistic publications that have already accustomed to the communication between the "citizens" of the media. As an example is The Jakarta Post which has a specific rubric for Letter to Editor (LtE) which is very passionate. Hans Selye once wrote one of the legendary Letter to Editors (LtEs), and that letter opened the way for scientific studies on stress. Therefore, ANIMA Indonesian Psychological Journal encourages the readers to send their extraordinary ideas through Letter to Editor (LtE). Following up on this invitation, we will hold activities and develop supporting products. The existence of training, assistance, and guidelines for writing Letter to Editor (LtE) is expected to foster Letter to Editor (LtE) writing habits as an alternative to quality publications, and not as a new variant of academic integrity deviations. Di bidang psikologi, kita menyaksikan dan mengalami perkembangan pesat gagasan tentang manusia, terutama di era Revolusi Industri 4,0, ketika psikologi akan menerima pengaruh gagasan sibernetika. Sebagai peneliti psikologi yang tekun mengamati perilaku manusia, tentu berulang kali terbesit dalam benak kita, berbagai “hipotesis” tentang dinamika kompleks perilaku manusia. Terutama di Indonesia, tempat subur di mana dinamika kompleks itu dibalut dengan keanekaragaman budaya hidup. Sangat mendesak untuk menerbitkan sejumlah “besit hipotetis” itu - juga respons terhadap hasil studi sejawat - dalam bentuk yang padat, komunikatif, dan persuasif; sehingga dapat ditindaklanjuti para sejawat dengan senang hati. Inilah salah satu jalur pengembangan sains psikologi yang, secara jujur dan menyesal, masih langka ditapaki oleh jurnal ilmiah psikologi di Indonesia. Cara kita mengkomunikasikan sains psikologi, dengan demikian, tidak memadai lagi "ditampung" oleh satu atau dua bentuk publikasi ilmiah, seperti artikel orisinal atau reviu (baik naratif maupun sistematik). Dunia publikasi ilmiah Indonesia dapat belajar dari dunia publikasi jurnalistik yang telah lebih dahulu membiasakan kekomunikatifan antar-"warga" media tersebut. Sebagai contoh adalah The Jakarta Post yang memiliki rubrik spesifik Letter to Editor (LtE) yang sangat bergairah. Hans Selye pernah menulis salah satu Letter to Editor (LtE) yang legendaris, dan suratnya membuka jalan bagi studi ilmiah tentang stres. Maka dari itu, ANIMA Indonesian Psychological Journal mendorong pembaca untuk mengirimkan ide luar biasa mereka melalui Letter to Editor (LtE). Menindaklanjuti undangan ini, kami akan menyelenggarakan kegiatan dan mengembangkan produk pendukung. Adanya pelatihan, pendampingan, dan pedoman penulisan Letter to Editor (LtE) diharapkan dapat menumbuhkan kebiasaan penulisan Letter to Editor (LtE) sebagai alternatif publikasi berkualitas, dan bukan sebagai varian baru penyimpangan integritas akademik.